Pemanfaatan Media Sosial sebagai Sarana Promosi Aneka Produk yang Dihasilkan UMKM di Desa Muara Talang: Utilization of Social Media as a Means of Promotion of Various Products Produced by MSMEs in Muara Talang Village - Harlina Kurniaty; Lisawanto Lisawanto; Muhammad Emil Salim Nugraha (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2023)
The government always supports various uses of digital-based technology, which aims to increase the productivity of MSMEs. This social media aims to disseminate messages online about how user activities consume products from the micro, small and medium enterprises (MSMEs) sector. MSME actors have changed their marketing orientation due to the pandemic, and many have turned to electronic commerce (e-commerce) to increase sales. Based on initial observations, MSMEs in Muara Talang village are still using conservative methods in marketing their products to answer the partner problems above and skills training is provided for them. MSMEs in Muara Talang Village, South Barito Regency, about how to make and use social media as an effective and efficient means of selling/promoting products to increase the marketing of their products in the form of types of social media that are widely used to promote and sell MSMEs products.